Use of the Kano model and conjoint analysis to evaluate attributes affecting restaurateur preferences for fresh pork products - Mahatthanachosit, N. (2024)
This paper studies a company that is a manufacturer and distributor of a range of food products aimed at general consumers, as well as restaurant and hotel businesses. The company has a need to develop and improve its fresh pork products to best meet the requirements of a group of customers, who are restaurateurs in Chiang Mai province, Thailand, with a plan to increase its market share, which is currently low in this segment. The Kano model, combined with conjoint analysis (CA), was used to study the attributes that have an effect on restaurateur preferences in making purchase decisions for fresh pork products. The study was conducted in two principal phases. The first phase is an analysis using the Kano model to arrive at the attributes and attribute levels of the fresh pork products. The six attributes obtained are then used further in the second phase, which is the CA, to find the attributes that have an effect on customer preferences in decisions to purchase fresh pork products. In the CA part of this study, data were collected from 100 restaurateurs in Chiang Mai. It was found that the attributes most important to restaurateurs were freshness and cleanliness (very fresh and clean), followed by standards certification labelling (government guarantee of quality), the colour of pork (pinkish-red), the amount of fat (3%), the price (125 Thai baht/kg) and the slicing method (sliced by machine).